Development of hydrogen fuelled transport engine and field tests on vehicles - Krishnan Unni, Jayakrishnan; Govindappa, Premakumara; Das, Lalit Mohan (International journal of hydrogen energy, 2017)
Three wheelers have been employed as a common transport vehicle in many developing countries. The present work discusses the test results on a single cylinder typical three-wheeler vehicular engine in lab and subsequent development of Hydrogen fuelled three wheelers. The paper also highlights the modifications done on the test rig to ensure smooth operation without any undesirable combustion phenomena such as backfire and rapid rate of pressure rise. The engine was developed for bi-fuel operation with modifications required in the existing designs of gasoline engine to achieve hydrogen operation. Performance and exhaust emission characteristics of the engine were experimentally evaluated to meet the requirements for vehicular operation. The engine developed peak torque of 13.2 Nm@3200 rpm while operating at lean conditions. Development of fifteen hydrogen-fuelled three wheelers equipped with various safety features are also discussed in the paper. •Single cylinder engine was modified for hydrogen and gasoline bi-fuel operation.•The engine performance and emission characteristics were optimized for hydrogen operation.•The optimized engines were used in a fleet of three wheelers used for public transport.•The hydrogen supply layout and safety feature of the vehicle developed is described.•Field trials of vehicles are currently undergoing in a popular public gathering place in New Delhi, India.